FedEx delivers : how the world's leading shipping company keeps innovating and outperforming the competition - Birla, Madan (John Wiley & Sons, 2005)
An inside look at leadership practices that enabled the world's leading shipping company to outthink and outperform its competitionUsing firsthand accounts from top leaders at FedEx, FedEx Delivers explains how the company became an international powerhouse and one of the most trusted global brands by using leadership practices that tapped into the creativity and commitment of its employees.